The Holocaust, medicine and becoming a physician: the crucial role of education - Reis, Shmuel P.; Wald, Hedy S.; Weindling, Paul (Israel journal of health policy research, 2019)
Learning about the abandonment of moral principles of healthcare professionals and scientists, their societies and academic institutions, to a murderous ideology yields fundamental concerns and global implications for present and future healthcare professionals’ education and practice. Medicine’s worst-case scenario raises deeply disturbing yet essential questions in the here and now: Could the Holocaust, one of the greatest evils ever perpetrated on humankind, have occurred without the complicity of physicians, their societies, and the scientific profession community? How did healers become killers? Can it happen again? We reflect here on those queries through the lens of the Second International Scholars Workshop on Medicine during the Holocaust and Beyond held in the Galilee, Israel on May 7–11, 2017 and derive contemporary global lessons for the healthcare professions. Following a brief historical background, implications of the history of medicine in the Holocaust are drawn including 1) awareness that the combination of hierarchy, obedience, and power constitutes a risk factor for abuse of power in medicine and 2) learning and teaching about medicine in the Holocaust and beyond is a powerful platform for supporting professional identity formation. As such, this history ideally can help “equip” learners with a moral compass for navigating the future of medical practice and inherent ethical challenges such as prejudice, assisted reproduction, resource allocation, obtaining valid informed consent, end of life care, and challenges of genomics and technology expansion. Curriculum modules are available and studies on impact on students’ attitudes and behavior are emerging. The conference culminated with the launch of the Galilee Declaration, composed and signed by an international, inter-professional community of historians, healthcare professions educators, and ethicists. The Declaration included herein ( http://english.wgalil.ac.il/category/Declaration ) calls for curricula on history of healthcare professions in the Holocaust and its implications to be included in all healthcare professions education.